2017
DOI: 10.22456/1679-9216.79777
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Echocardiographic Parameters of Dogs with Chronic Mitral Valve Regurgitation Treated with Amlodipine or Pimobendan

Abstract: Background: Chronic mitral valve regurgitation is the most common heart disease in dogs. It is caused by myxomatous mitral valve degeneration, an acquired degenerative disease that can lead to congestive heart failure. Pimobendan is a mixed action drug, with inotropic and vasodilator proprieties, widely used to treat such dogs. Amlodipine is a pure vasodilator drug used as an anti-hypertensive agent, with no inotropic effects. This study aimed to compare  echocardiographic, electrocardiographic and blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Consistent with previous reports, we found that our recruited MMVD dogs in this study are small breeds and aged dogs ( 1 3 ). These dogs were classified based on ACVIM guidelines ( 4 ), in which LA/Ao ratio and LVIDDN from echocardiography were used to differentiate stage B1 from B2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous reports, we found that our recruited MMVD dogs in this study are small breeds and aged dogs ( 1 3 ). These dogs were classified based on ACVIM guidelines ( 4 ), in which LA/Ao ratio and LVIDDN from echocardiography were used to differentiate stage B1 from B2.…”
Section: Discussionsupporting
confidence: 93%
“…The most commonly acquired cardiac disease in dogs is a myxomatous mitral valve disease (MMVD) ( 1 ). Mitral valves (MVs) can undergo degenerative pathologic changes due to many factors including genetics ( 2 ) and age ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In dogs with MMVD in stage B2, pimobendan, a phosphodiesterase inhibitor with positive inotropic and vasodilator effects, is the recommended treatment; however, the drug is expensive and can produce adverse effects. In a double-blind study, pimobendan and amlodipine, a calcium channel blocker, showed no statistically significant changes in SBP in dogs after 60 days of therapy, 26 corroborating the study where administration of pimobendan did not reduce SBP during 512 days of treatment. 27 Crataegus has been shown to have a positive inotropic effect due to an increase in the resting potential, 28 corroborated by this study, in which FS increased with a statistically significant outcome in the homeopathy group, compared with the other groups, confirming the improvement in ventricular function.…”
Section: Discussionsupporting
confidence: 71%